European motorways of the sea: lessons from the Spanish experience. (1st January 2012) - Gesé Aperte, Xavier; Baird, Alfred J.
Several motorways of the sea (MoS) linking Spain with nearby states have developed over recent years. These services have succeeded in shifting freight from road to sea. Services evolved through private enterprise, albeit now receiving public support to help level the playing field with road subsidies. Other services are assisted through public tenders and financial incentives. This study investigates development of three MoS services, their impacts, characteristics, and challenges competing against road transport. MoS services now link both the Mediterranean and Atlantic coasts of Spain with neighbouring states. Learning from experiences of MoS services in Spain holds important lessons for MoS start-ups elsewhere in Europe and further afield. Findings contribute to the literature not least in presenting a new definition of MoS, this considered even more relevant given the effects of the economic crisis. Results should assist policymakers refine and improve policies with respect to MoS development.